The effect of Bacillus subtilis and its delivery route on hatch and growth performance, blood biochemistry, immune status, gut morphology, and microbiota of broiler chickens - Samson Oladokun; Deborah Adewole (Poultry Science, 2023)
ABSTRACT: This study evaluated the effect of probiotics (Bacillus subtilis fermentation extract) and its delivery route (in-feed or in ovo) on hatch and growth performance, blood biochemistry, immune status, gut morphology, and microbiota of broiler chickens. Hatching eggs were incubated for 21 d. On d 12, viable eggs were randomly allotted to 4 groups: the noninjected, in ovo saline (S), in ovo Bacillus subtilis 1 (P1), and in ovo Bacillus subtilis 2 (P2). On d 18, S, P1, and P2 groups received 0.2 mL saline diluent, 10 × 106, and 20 × 106 CFU of the bacterium via the amnion, respectively. At hatch, chicks were re-allotted to 5 new treatment groups: P1, P2, 0.005% in-feed Bacillus subtilis extract (P3), 0.05% in-feed bacitracin methylene disalicylate (BMD,), and corn-wheat-soybean diet negative control (NC) in 9 replicate pens (22 birds/pen) and raised for 35 d. Hatch parameters were assessed on d 0, and growth performance indices measured weekly. On d 25, 1 bird/cage was euthanized, and samples collected for further analysis. Data were analyzed by generalized linear model. Treatments S and P2 recorded higher (P = 0.01) chick BW/ Egg Weight values compared to the non-injected eggs. P3 and P2 reduced (P = 0.02) FI at week 5 compared to the NC treatment. However, no change in average body weight gain (ABG) and feed conversion ratio (FCR) were observed during the same period. At d 35, while BMD treatment showed a tendency (P = 0.09) to increase FI compared to the NC treatment, ABG and FCR were similar for all treatments. Blood sodium and chloride levels were increased (P < 0.05) by the BMD treatment compared to the NC treatment. Compared to other treatments, BMD and P3 treatments increased (P < 0.001) jejunal and ileal villus height to crypt depth ratios, respectively. However, P1 and P2 increased (P < 0.001) villus height to crypt depth ratio in the duodenum compared to NC treatment. Treatments did not affect gut microbial diversity; however, BMD treatment increased (P < 0.05) the proportion of bacteria in the genus Enterococcus in the ileum and reduced (P < 0.05) the proportion of bacteria in the genus Streptococcus in the ceca. All probiotics treatments (irrespective of route and dose) reduced (P < 0.001) the levels of serum IgG compared to the NC treatment. However, P1 and P2 had the lowest numerical decrease in serum IgG concentrations, suggesting that Bacillus subtilis (especially in ovo delivered) might provide broiler chickens with better immunological protection by neutralizing pathogenic organisms that could result in the production of natural antibodies.